TWO FACES OF THE QUATERNARY BENZO[C]PHENANTHRIDINE ALKALOID SANGUINARINE - Ulrichova, J.; Simanek, V. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Mechanistic studies on normal or cancer cells testify to the effects of sanguinarine (SG) on apoptosis, angiogenesis, proliferation, differentiation and transformation. In vivo SG displayed mainly antimicrobial and anti-inflammatory effects. On the other hand, a well-known toxic effect attributed to SG and its dihydroderivative (DHSG) is “The Epidemic Dropsy Syndrome”. SG has been reported to form DNA adducts in vitro and increase the levels of DNA single strand breaks in blood and bone marrow of mice treated i.p. with SG. The weakess of safety/toxicity SG and/or DHSG assessment has been the absence of data on the pharmacokinetics, biodistribution, metabolism and the possible genotoxicity in vivo. SG pharmacokinetics was studied in the rat after a single oral dose (10 mg.kg-1 body weight). Alkaloid determination in plasma and liver was carried out by the validated HPLC/ESI-MS method. The pharmacokinetic parameters (tmax, cmax, AUC0?t and AUC0??) were determined for SG. The major metabolite detected in plasma was DHSG. Neither SG nor DHSG were detected in the urine. The formation of the less toxic DHSG might be the first step of SG transformation in the organism and its subsequent elimination in phase II reactions. Both compounds were completely eliminated from plasma and liver after 24 h. Benz[c]acridine, the only SG metabolite referred to in the literature, was not detected in the plasma, liver or urine. The rats consumed ad libitum either the standard diet or the diet containing 367 ppm of SG and chelerythrine (sanguiritrin) for 90 days. The DNA adduct formation in liver was analyzed by 32P-postlabeling technique and DNA single strand breaks in lymphocytes were evaluated by Comet assay. The results showed that sanguiritrin induced no DNA damage to rat lymphocytes or hepatocytes after 90 days oral administration. Data from the studies described confirms the reduction of SG to DHSG in mammals and that orally administered SG displays no DNA damage. Acknowledgements: This work was supported by the Grant Agency of the MSMT (grant No. MSM 6198959216) and by the Grant Agency of the Czech Republic (GA CR 525/07/0871).